The SETDB1 histone methyltransferase is recurrently amplified in and accelerates melanoma - Ceol, Craig J. (2011)
The most common mutation in melanoma, BRAF(V600E), activates the BRAF serine/threonine kinase and causes excessive MAPK pathway activity(1,2). BRAF(V600E)mutations are also present in benign melanocytic nevi(3), highlighting the importance of additional genetic alterations in the genesis of malignant tumors. Such changes include recurrent copy number variations that result in the amplification of oncogenes(4,5). For certain amplifications, the large number of genes in the interval has precluded an understanding of cooperating oncogenic events. Here, we have used a zebrafish melanoma model to test genes in a recurrently amplified region on chromosome 1 for the ability to cooperate with BRAF(V600E) and accelerate melanoma. SETDB1, an enzyme that methylates histone H3 on lysine 9 (H3K9), was found to significantly accelerate melanoma formation in the zebrafish. Chromatin immunoprecipitation coupled with massively parallel DNA sequencing (ChIP-Seq) and gene expression analyses revealed target genes, including Hox genes, that are transcriptionally dysregulated in response to elevated SETDB1. Our studies establish SETDB1 as an oncogene in melanoma and underscore the role of chromatin factors in regulating tumorigenesis.